Upper and lower bounds on the creep strain and stress relaxation induced by interface diffusion in metal-matrix particulate composites. (1st May 2021) - Xu, Binbin; Guo, Fenglin
Highlights: Obtain upper and lower bounds on diffusional creep strain and stress relaxation. Offer an alternative approach to analyze creep behavior of MMCs with complex distribution. Find that the diffusional properties of the interface only affect the rate of diffusional creep strain. Abstract: In this study, we developed a micromechanics scheme to predict the upper and lower bounds on the creep strain and stress relaxation induced by interface diffusion in metal-matrix particulate composites. The normal stress acting on the matrix-inclusion interface, which is the driving force for interface diffusion, is estimated by using the Hashin-Shtrikman bounds and mean-field micromechanics theory. Analytical solutions of upper and lower bounds on the creep strain under constant stress and the relaxed stress at fixed strain are obtained. Results of this work show that the ultimate creep strain and relaxed stress are only related to the material properties and the percentage of each component, such as volume fraction of inclusion and elastic modulus ratio of inclusion to matrix. The parameters of interface diffusion only influence the rate of creep strain. It is found that the creep deformation and stress relaxation of composites are more sensitive to the volume fraction of inclusion than the elastic modulus ratio. The methodology of this study also applies to analysis of creep deformation of composites where both the matrix creep and interface diffusional creep need to be considered. The present study offers new perspectives for in-depth understanding of creep behavior of composites driven by mass diffusion along inclusion-matrix interface.